EVALUATION OF THE MORPHOMETRICAL ELEMENTS OF RELIEF IN THE PROCESS OF RUNOFF: (on the example of Debed River) (Proceedings of the YSU C: Geological and Geographical Sciences, 2004)
In the article the point of issue is the evaluation of influence of the morphometrical elements of relief in the process of runoff. The local correlations between the coefficient of low and middle elevations of water intake, horizontal and deep dissections, expositions and slopes arc received. These correlations can be used while giving the characteristic of runoff of the unexamined rivers.
Keywords: morphometrical elements; characteristic of runoff; unexamined rivers